Absolute Insurer Denial of Direct-Acting Antiviral Therapy for Hepatitis C: A National Specialty Pharmacy Cohort Study - Gowda, Charitha (Open Forum Infect Dis, 2018)
BACKGROUND: Despite the availability of new direct-acting antiviral (DAA) regimens, changes in DAA reimbursement criteria, and a public health focus on hepatitis C virus (HCV) elimination, it remains unclear if public and private insurers have increased access to these therapies over time. We evaluated changes in the incidence of absolute denial of DAA therapy over time and by insurance type. METHODS: We conducted a prospective cohort study among patients who had a DAA prescription submitted from January 2016 to April 2017 to Diplomat Pharmacy, Inc., which provides HCV pharmacy services across the United States. The main outcome was absolute denial of DAA prescription, defined as lack of fill approval by the insurer. We calculated the incidence of absolute denial, overall and by insurance type (Medicaid, Medicare, commercial), for the 16-month study period and each quarter. RESULTS: Among 9025 patients from 45 states prescribed a DAA regimen (4702 covered by Medicaid, 1821 Medicare, 2502 commercial insurance), 3200 (35.5%; 95% confidence interval, 34.5%–36.5%) were absolutely denied treatment. Absolute denial was more common among patients covered by commercial insurance (52.4%) than Medicaid (34.5%, P < .001) or Medicare (14.7%, P < .001). The incidence of absolute denial increased across each quarter of the study period, overall (27.7% in first quarter to 43.8% in last quarter; test for trend, P < .001) and for each insurance type (test for trend, P < .001 for each type). CONCLUSIONS: Despite the availability of new DAA regimens and changes in restrictions of these therapies, absolute denials of DAA regimens by insurers have remained high and increased over time, regardless of insurance type.